Selective expression of human X chromosome-linked green opsin genes. - Winderickx, J (1992)
The human red and green photopigments are specified by genes on the long arm of the X chromosome (Xq28). In individuals with normal color vision, the locus was proposed to consist of a single red pigment gene upstream of one or more copies of green pigment genes. The presence of a single red pigment gene in the array was confirmed by demonstration of only one retinal mRNA transcript coding for the red opsin. In individuals with multiple green pigment genes, it is unknown whether all genes are expressed. We analyzed the sequence of red- and green-specific mRNA from retinas of individuals with multiple green pigment genes in comparison with the corresponding genomic DNA sequences. The data showed that only a single green pigment gene is expressed. We therefore suggest that a locus control-like element, already known to be located 3.8 kilobases upstream of the transcription initiation site of the red pigment gene, allows transcription of only a single copy of the green pigment genes, probably the most proximal copy. This finding provides an explanation for the not-infrequent presence of 5' green-red hybrid genes in individuals with normal color vision. Such hybrid genes are usually associated with defective color vision. We suggest that 5' green-red hybrid genes produce defective color vision only when their position in the gene array allows expression in the retinal cone cells.